Ethno-STEAM Based E-Comic “Lilis Lamiang”, is it Necessary to Use it on Science Learning in Elementary Schools? - Wndari Sabella; Fathul Zannah (Postgraduate, University of Mataram, 2024)
This research aims to analyze the response to the needs of ethno-STEAM based e-comic “lilis lamiang” for elementary school students. In this study we focus to analyze the teacher and student perception about the development of the local wisdom module, especially to increase learning outcome. The research method is descriptive and qualitative by used surveys to collect data. Data collection was carried out by distributing questionnaires to 2 elementary school teacher and to 20 student 5th grade students, SDN 4 Menteng in Palangkaraya City, Central Kalimantan. The collected data were analyzed using descriptive analysis. The results of this research showed that teachers have never developed their own teaching materials based on local potential in Central Kalimantan, while students are of the opinion that the use of teaching materials based on local potential will make learning activities more interesting. This research concluded that the development of etno-STEAM based e-comic especially about lilis lamiang very important thing to do based on teacher and student perception and important to continue in the next research to develop the module.